Bezpieczeństwo Budowli w Świetle Korelacji Zachodzącej Między Granicą Plastyczności i Wytrzymałości - Piekarski, W. (Engineering Transactions, 1962)
According to the semi-probabilistic method for determining the coefficient of safety, the safety of a structure may be determined in relation to the yield point, the strength or the yield point and the strength taken together. In the third case where the safety factor is determined in relation to the yield point Q and where the by yield point is reached before the structure collapses, the safety of the structure is assured by the strength R. This is a certain safeguard of the structure and the difference D = R – Q [the Eqs. (6) and (21)] may constitute a measure of safety. Making use of the relation (correlation) = F(Q) [Eq. (9)] the strength R for a given yield point Q. Similary, by means of the equation of regression of Q in relation to R: Q = f (R) [Eq. (13)], we can foretell the yield point for a given strength R. As an illustration of the theoretical considerations, investigations of a structural steel has been carried out. It is described in the present paper.